Prevalence and risk factors of intestinal parasitic infections in a tertiary care teaching hospital - Zarine Khan; Tarana Sarwat; Riti Srivastava; Dalip K. Kakru (Journal of Krishna Institute of Medical Sciences University)
Background: Infections due to intestinal parasites are a major public health concern in developing countries contributing to morbidity as well as mortality in the population. Aim and Objectives: A hospital-based cross-sectional study was done to determine the prevalence of intestinal parasites and association with different risk factors. Results: The total prevalence was found to be 15%, with protozoans being more common (63%) than helminths (33%). Cyst of Entamoeba histolytica/dispar was the most common protozoan and Ascaris was the most common helminth isolated. Rural residence, open defecation and barefoot walking were significantly associated (p < 0.05) with the prevalence. Conclusion: Along with mass deworming and elimination program being carried out by the government, results of this study would help in planning and implementing specific policies in the area.